Dinamika Implementasi Kurikulum Adaptif: Perspektif Guru dan Siswa di Sekolah - Ahmad Fauzi Maarif; Siti Nur Azizah; Muhammad Rizal Hakim (Genta Bangsa : Jurnal Ilmu Pendidikan, 2026)
Adaptive curriculum implementation has become a critical discourse in Indonesian education reform, particularly following the Merdeka Belajar policy initiative. However, empirical studies examining the dynamics of implementation from the dual perspectives of teachers and students remain scarce. This study aims to explore and analyze the dynamics of adaptive curriculum implementation as experienced by teachers and students in Indonesian schools. A qualitative phenomenological approach was employed, involving fifteen participants comprising eight teachers and seven students from various school levels in South Lampung District. Data were collected through in-depth interviews, classroom observations, and document analysis. Findings reveal four key dimensions: teacher readiness and adaptation strategies, student responses and engagement dynamics, institutional support mechanisms, and barriers to sustainable implementation. Results indicate significant gaps between policy intentions and classroom realities. The study concludes that successful adaptive curriculum implementation requires systemic support, continuous professional development, and genuine student-centered pedagogical transformation.